PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ARTICULATE STORYLINE BERMUATAN JARIMATIKA PERKALIAN UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG PADA MATA PELAJARAN MATEMATIKA KELAS IV - Nisa Andawiyah, Kurratul; Pratiwi, Siska (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Students' perception of mathematics is a difficult lesson that is still often encountered, especially in multiplication materials. This condition can be even more complex if learning is not supported by interesting and innovative media. The purpose of this study is to develop an interactive learning media based  on articulate storylines loaded with multiplication arithmetic and analyze its effectiveness in improving students' numeracy skills. The methodological research employed in this study is anchored in Research and Development (R&D), utilizing the ADDIE model, which encompasses five distinct phases: analysis, design, development, implementation, and evaluation. The instruments used are observation sheets for the implementation of learning and tests. The results of the small group test and the large group test showed that the students' learning completeness reached 100% and the implementation of learning went well. Therefore, it can be concluded that the interactive learning media developed was declared effective in encouraging the improvement of the numeracy skills of grade IV students of SDN Pejagan 1 Bangkalan.